2010
DOI: 10.1103/physrevlett.105.257206
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Intrinsic Limit to the Charge-Carrier-Induced Increase of the Curie Temperature of EuO?

Abstract: Rare earth doping is the key strategy to increase the Curie temperature (T(C)) of the ferromagnetic semiconductor EuO. The interplay between doping and charge carrier density (n), and the limit of the T(C) increase, however, are yet to be understood. We report measurements of n and T(C) of Gd-doped EuO over a wide range of doping levels. The results show a direct correlation between n and T(C), with both exhibiting a maximum at high doping. On average, less than 35% of the dopants act as donors, raising the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 27 publications
15
73
0
Order By: Relevance
“…9 Recent studies of spin-resolved x-ray absorption spectroscopy have shown a spin-split conduction band of about 0.6 eV in its ferromagnetic state, creating a nearly 100% spin polarized electrons close to the conduction band edge. 10 Although the stoichiometric EuO has a Curie temperature (Tc) of 69 K, Tc can be enhanced significantly by pressure, [11][12][13] interfacial strain 14 or electron doping via rare-earth atoms [15][16][17][18][19][20][21][22][23][24] or oxygen vacancies. 15,16,[23][24][25] The integrations of EuO with Si, 18,[23][24][25][26][27] GaAs, 28 and GaN 18 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent studies of spin-resolved x-ray absorption spectroscopy have shown a spin-split conduction band of about 0.6 eV in its ferromagnetic state, creating a nearly 100% spin polarized electrons close to the conduction band edge. 10 Although the stoichiometric EuO has a Curie temperature (Tc) of 69 K, Tc can be enhanced significantly by pressure, [11][12][13] interfacial strain 14 or electron doping via rare-earth atoms [15][16][17][18][19][20][21][22][23][24] or oxygen vacancies. 15,16,[23][24][25] The integrations of EuO with Si, 18,[23][24][25][26][27] GaAs, 28 and GaN 18 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…We see that in the vicinity of T C the rotation decreases drastically and reflects the decrease of M z . Note that the onset temperature of the magnetization in EuO is strongly influenced by external magnetic fields, 15,25 which explains the small signal remaining just above T C . Contributions by the LFR that may interfere with the third-order rotation are small.…”
Section: B Sample Preparation and Experimental Methodsmentioning
confidence: 99%
“…12 It has a high potential for semiconductor-based spintronics applications [12][13][14][15] due to its half-metallic behavior with electron doping [12][13][14] and its structural and electronic compatibility with Si, GaN, and GaAs. 12,16 At room temperature, stoichiometric EuO is a paramagnetic semiconductor with a band gap of ∼1.2 eV.…”
Section: A Ferromagnetic Euomentioning
confidence: 99%
“…15) and 170 K. 14 Films doped with lanthanum have a maximum reported T C between 118 K (Ref. 1) and 200 K. 10 Likewise, for films doped with iron, the reported T C varies between 88 K and 200 K. 6,7 For Gd-doped films grown in an adsorption-controlled regime, however, the Curie temperatures are consistent and similar, 15,16 conceivably due to a minimized amount of oxygen vacancies realized in this particular growth regime. 23 In this letter, we report the behavior of an unexplored dopant for EuO, lutetium, which enhances the T C in epitaxial films grown in an adsorption-controlled regime.…”
mentioning
confidence: 96%
“…The interaction between the Eu f-electrons and the dopant electrons enhances the ferromagnetic exchange energy 4,5 and results in an increased T C . To date, this has been accomplished through the use of trivalent cations including iron, [6][7][8] lanthanum, 1,9,10 gadolinium, [11][12][13][14][15][16][17] and holmium. 9 Alternatively, the T C can be increased by deliberately making oxygen-deficient EuO such that the resulting oxygen vacancies donate an electron.…”
mentioning
confidence: 99%